From vulnerable to resilience: an assessment of small-scale fisheries livelihood in South Malang of Indonesia - Puji Handayati; Ahmad Munjin Nasih; Indah Susilowati; Idris; Prateep Kumar Nayak; Bagus Shandy Narmaditya (Discover Sustainability)
Abstract The livelihoods of small-scale fisheries in South Malang of Indonesia are being notably influenced by ecosystem degradation and climate change. Therefore, this study aims to investigate the vulnerability of small-scale fisheries in South Malang of Indonesia using the livelihood vulnerability index. The livelihood vulnerability was estimated using five major components and 20 sub-components. The data were obtained from small-scale fisheries in South Malang of Indonesia through questionnaires directed to the respondents using simple random sampling. The findings indicate that two main components (livelihood strategy and climate variability and natural disaster) were included in high vulnerability, while another two main components (sociodemographic and social network) were categorized as moderate vulnerability. The sensitivity components, including access to water, electricity, and health) were perceived as low vulnerability. Based on the findings of this study, it recommends that policymakers need to develop policies and campaigns regarding climate awareness and adaptation strategies by small-scale fisheries.